Radiographic Study on the Fetal Development of the Mandibular Condyle: by a Mento-Vertical Cephalography - SHIMAMURA, Takuya; SAIRENJI, Eiko; IKEDA, Minato; KAWASHIMA, Shoji; KITAGAWA, Tadashi; OHSHIMA, Kazuo; SHIMADA, Kazuyuki; HONDA, Kazuya; MARUHASHI, Kazuo; KIMURA, Kazuyuki; SHINODA, Koji (Journal of the Japanese Society for the Temporomandibular Joint, 1991)
The development of the human mandibular condyle is one of the most important topics in dentistry and the subject of much current research. However, little has been published on th development of the mandibular condyle during the fetal period, and in particular studies based on radiographic examination are almost nonexistens. Under the circumstances the present study of the 5 to 10 months old fetus was undertaken clarify the development of the fetal mandibular condyle. The study was undertaken on 33 Japanese fetuses of between 5 to 10 months that had been preserved in formalin in the 1st Department of Anatomy, Nihon University School of Dentistry. The ages of the fetus were determined by applying of Haase's method from crown-heel length measurements. Image measurements were made from radiographs using the method described by Toriumi and Sawada. Mento-Vertical Cephalography films were placed on a film viewer to trace an outline of the condyle. Then the long axis, the short axis, the maximum distance between the lateral poles of the condyles, the area of the condyle and the angle formed by the corrected axial plane of the two condyles were measured by a digitizer connected to a computer. The results were as follows 1. The long and short axes, the maximum distance between the lateral poles of the condyles and the area of condyle in the Mento-Vertical Cephalography view show an almost linear development with increased fetal ages during the period 5 to 9 months. This linear development makes a spurt from the 9th month, with no significant difference between the sides. 2. The angle formed by the corrected axial plane of the two condyles of 5 to 10 month old fetuses was about 120 degrese, showing almost no change with increased fetal age.